PENGEMBANGAN E-BOOK BERBASIS CANVA MATERI MENGENAL DAN MENGEKSPLORASI ANEKA ANYAMAN PELAJARAN SENI RUPA KELAS V SDN 2 DOPLANG KABUPATEN BLORA - Dyah, Afifah; Setiawan, Deni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop teaching materials in the form of Canva-based e-books and determine their feasibility and effectiveness in improving creative thinking skills in students. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, planning, product development, validation by subject matter experts and media experts, limited testing, product revision, and implementation in learning. This study involved fifth-grade students at SDN 2 Doplang, Blora Regency, as research subjects. Data in this study were collected using observation, interviews, questionnaires, and learning outcome tests. The results showed that the Canva-based e-book was deemed feasible for use based on the assessment results of subject matter experts and media experts, with a rating of highly feasible. The use of Canva-based e-books was able to optimize the activity and interest of students in learning, as well as their understanding of weaving material. In addition, there was an increase in students' creative thinking skills, as shown by more varied and innovative weaving works.